Variasi Bahasa Iklan Secara Offline di Malaka Kajian Sosiolinguistik - Maria Fatima Tae; Ofra Talelu; Selestina Niis; Yulita Abuk; Selestina Luruk Seran; Emeliana Tai (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The phenomenon of variations in slogan language in advertisements in Malacca district offline uses various languages ​​consisting of Latin, Tetum, Dawan and English. The seller's aims and objectives are conveyed briefly and concisely through the slogan and advertisement. The phenomenon of variations in advertising language will have an impact on people's understanding of offline site advertisements. The aim of this research is to determine the various variations of language used by sellers in promoting their merchandise. The method used in this research is qualitative description. The results of this study show that the phenomenon of using advertising language in Malacca district, especially on shopping sites, is increasingly diverse and gives rise to the phenomenon of language variations. However, in reality, not all people understand the forms of language variation and the function of language variation. In this research, variations in advertising language were identified, for example English, slang or social languages. The functions of language variations identified are informative function, directive function and expressive function. The advertising language used by online shopping sites should be able to provide clear information and be easily understood by the public so that goals can be achieved.